Properties and Limitation of an Oxide Coated Aluminum Brake Rotor - Gulden, Florian; Gramstat, Sebastian; Stich, Anton; Höppel, Heinz Werner; Tetzlaff, Ulrich (SAE Technical Papers, 2018)
The electrification of the powertrain and the thereto related recuperation of the electric engine saves the energy in the battery and thus reduces the thermally dissipated brake energy, which leads to lower brake rotor temperatures compared to combustion engine vehicles (ICEVs). These new conditions enable to reconsider brake disc concepts. Including lightweight design in heavy battery electric vehicles (BEVs) and the increasingly reliant corrosion resistance of brake rotors, Aluminum is a promising approach for new brake disc concepts. In the past, Aluminum brake disc concepts have already been deployed. For instance Aluminum Metal-Matrix Composite (Al-MMC) concepts in the Lotus Elise S1 and on the rear axle of the Volvo V40 [1]. The presented concept is a different approach and separates the friction system from the bulk Aluminum brake disc, achieved by coating of the friction rings. By locally reinforcing the friction rings, the good machinability and ductility of the base body is maintained and simultaneously the friction surface is sufficiently protected to resist the frictional loading during a brake application. In this work, fundamental studies on a brake dynamometer were conducted and supplemented by microstructural investigation to identify damage mechanisms and to judge the technical application of the concept.
Created from Fastlane, Scopus look-up